MICAL2 Facilitates Gastric Cancer Cell Migration via MRTF-A-Mediated CDC42 Activation - Wang, Yueyuan; Min, Pengxiang; Qi, Chenxiang; Zhao, Shuo; Yu, Minjie; Zhang, Yujie; Du, Jun (Frontiers in Molecular Biosciences, 2021)
Aims and hypothesis: Cell migration is driven by the reorganization of the actin cytoskeleton. Although MICAL2 is known to mediate the oxidation of actin filaments to regulate F-actin dynamics, relatively few studies have investigated the potential role of MICAL2 during cancer cell migration. Methods: The migratory ability of gastric cancer cells was measured by wound healing and transwell assays. The relationship between MICAL2 expression and MRTF-A nuclear localization was analyzed using gene overexpression and knockdown strategies. The production of reactive oxygen species (ROS) was evaluated by CM2-DCFHDA staining. mRNA and protein levels of MMP9 were measured using qPCR and immunoblotting analysis. The activities of CDC42 and RhoA were assessed using pulldown assays. Results: Depletion of MICAL2 markedly reduced gastric cancer cell migration. Mechanistically, silencing of MICAL2 inhibited the nuclear translocation of MRTF-A in response to EGF and serum stimulation, whereas the contents of MRTF-A remained unchanged. Further analysis showed that silencing of MICAL2 decreased the activation of CDC42 as well as mRNA and protein levels of MMP9. Ectopic expression of MICAL2 augmented MRTF-A levels in the nucleus, and promoted the activation of CDC42, MMP9 expression, and gastric cancer cell migration. Moreover, silencing of MRTF-A inhibited the CDC42 activation induced by overexpression of MICAL2. In addition, MICAL2-induced ROS generation contributed to the effect exerted by MICAL2 on MRTF-A nuclear translocation. Conclusions: Together, these results provide evidence that MICAL2 facilitates gastric cancer cell migration via positive regulation of nuclear translocation of MRTF-A and subsequent CDC42 activation and MMP9 expression.